2010
DOI: 10.1172/jci43127
|View full text |Cite|
|
Sign up to set email alerts
|

Tim-3 expression on PD-1+ HCV-specific human CTLs is associated with viral persistence, and its blockade restores hepatocyte-directed in vitro cytotoxicity

Abstract: Having successfully developed mechanisms to evade immune clearance, hepatitis C virus (HCV) establishes persistent infection in approximately 75%-80% of patients. In these individuals, the function of HCV-specific CD8 + T cells is impaired by ligation of inhibitory receptors, the repertoire of which has expanded considerably in the past few years. We hypothesized that the coexpression of the negative regulatory receptors T cell immunoglobulin and mucin domain-containing molecule 3 (Tim-3) and programmed death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
250
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(264 citation statements)
references
References 49 publications
13
250
1
Order By: Relevance
“…Previous studies have shown that HCV-specific CD8+ T cells from CHC patients exhibit reduced abilities to proliferate and secrete antiviral cytokines (Gruener et al, 2001;Wedemeyer et al, 2002). The potential contributors to such cellular dysfunction include the inhibitory signals mediated by PD-1 and Tim-3 (GoldenMason et al, 2009;McMahan et al, 2010), immunoregulatory cytokines and regulatory T cells. Moreover, blocking a single pathway, such as the PD-1 pathway, might be insufficient for immune reconstitution (Blackburn et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HCV-specific CD8+ T cells from CHC patients exhibit reduced abilities to proliferate and secrete antiviral cytokines (Gruener et al, 2001;Wedemeyer et al, 2002). The potential contributors to such cellular dysfunction include the inhibitory signals mediated by PD-1 and Tim-3 (GoldenMason et al, 2009;McMahan et al, 2010), immunoregulatory cytokines and regulatory T cells. Moreover, blocking a single pathway, such as the PD-1 pathway, might be insufficient for immune reconstitution (Blackburn et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…13). Indeed, exhausted virus-specific CD8 þ T cells also exhibit upregulation of Tim-3 in chronic lymphocytic choriomeningitis virus (LCMV) infection in mice (14) and in both HIV and hepatitis C virus infection in humans (15)(16)(17). However, whether the CD8 þ Tim-3 þ T cells in cancer are truly analogous to the exhausted T cells in chronic viral infection or whether they represent a different state of T-cell dysfunction that is unique to cancer remains an open question.…”
Section: Tim-3 In T Cells In Cancermentioning
confidence: 99%
“…Although it is clear that most, if not all, exhausted cells express high levels of PD-1, not all cells expressing high levels of PD-1 are exhausted (15). Other molecules such as 2B4 (CD244), lymphocyte-activation gene 3 (LAG-3), T-cell immunoglobulin domain and mucin domain 3 (Tim-3), and B-and T-lymphocyte attenuator (BTLA, CD272) also have been implicated as regulators of exhaustion (16)(17)(18). Although PD-1 blockade was able to restore function impressively to exhausted cells in mice infected with lymphocytic choriomeningitis virus (LCMV) (4), the effect of PD-1 blockade in humans has been less dramatic, and some T-cell functions were affected by PD-1 ligation much more profoundly than others (19)(20)(21).…”
mentioning
confidence: 99%